Teenage girls at a Y-Teens slumber party - Unknown:::Creator::::::::::::
Photograph shows a group of eight teenage girls at a Y-Teens slumber party. They are in sleeping bags with pillows arranged in a circle. Their heads are facing inward toward one another and most of the girls are awake.